The Bond of Mother and Child in the Lyrics of the Song Linked by Nadin Amizah (Semiotic Analysis of Roland Barthes) - Mutiara Umami Ningsih Mutiara; Muhammad Alfikri Matondang (Dinasti Publisher, 2024)
Music is a creative medium that people use to communicate their emotions and worldview. Through song lyrics and accompanying video clips, someone uses music to express opinions, feelings, or even social criticism. 'Bertaut' by Nadin Amizah is a song about someone's outpouring of emotions which has succeeded in capturing the audience's attention and winning various awards. Even though it was released a year ago,